2005
DOI: 10.4315/0362-028x-68.8.1729
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella enterica and Listeria monocytogenes Contamination in Foods of Animal Origin in Italy

Abstract: The present survey collected and analyzed the results of routine testing for Salmonella enterica and Listeria monocytogenes on foods of animal origin submitted for official controls in Italy during 2001 to 2002. Salmonella was detected in 2.2% of 71,643 food samples examined, and the isolation rates ranged from 9.9% for raw poultry meat to less than 0.1% for dairy products. Isolation rates were also high in raw pork (4.9%) and processed meats (5.3%), which often involved pork. Low rates were observed in seafoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 13 publications
8
46
1
2
Order By: Relevance
“…In the UK, Salmonella was detected in 1.7% of lamb, 1.1% of beef and 1.9% of pork samples (25). Other studies in the US and Italy also found the rate of Salmonella contamination to be higher in pork (3.3-9.9%) compared to beef products (1.0-1.9%) (26,27). The average Salmonella prevalences were 4.3 and 1.8% for pre evisceration and post intervention lamb carcasses, respectively (20).…”
Section: Discussionmentioning
confidence: 76%
“…In the UK, Salmonella was detected in 1.7% of lamb, 1.1% of beef and 1.9% of pork samples (25). Other studies in the US and Italy also found the rate of Salmonella contamination to be higher in pork (3.3-9.9%) compared to beef products (1.0-1.9%) (26,27). The average Salmonella prevalences were 4.3 and 1.8% for pre evisceration and post intervention lamb carcasses, respectively (20).…”
Section: Discussionmentioning
confidence: 76%
“…Very few studies have reported the occurrence of Campylobacter and L. monocytogenes in egg products (Izat and Gardner, 1988;Busani et al, 2005;Protais et al, 2007;Ohkochi et al, 2009;Rivoal et al, 2010;Sato and Sashihara, 2010). The reported incidence of Campylobacter and L. monocytogenes varied between countries and studies.…”
Section: Hazards Other Than Salmonellamentioning
confidence: 99%
“…A few studies have investigated the prevalence of L. monocytogenes on eggshells; they all found that samples tested negative for this pathogen (Adesiyun et al, 2005;Busani et al, 2005). Nevertheless, an investigation carried out in poultry flocks in France revealed that L. monocytogenes was present in 30 % of caged hen flocks (Chemaly et al, 2008).…”
Section: Hazards Other Than Salmonellamentioning
confidence: 99%
“…Studies worldwide have shown that Salmonella, Listeria, and Campylobacter are often present in pork carcasses and pork meat (Zhao et al, 2001;Whyte et al, 2004;Busani et al, 2005;Fosse et al, 2008). The prevalence of Salmonella spp., L. monocytogenes and Campylobacter spp.…”
mentioning
confidence: 99%